Basal Ganglia Gliosis in a Case of Rapid‐Onset Dystonia‐Parkinsonism (DYT12) with a Novel Mutation in ATPase 1A3 (ATP1A3). Issue 6 (19th May 2016) - Sampson, Jacinda B.; Michaeli, Tamar H.; Wright, Brenton A.; Goldman, James E.; Vonsattel, Jean‐Paul; Fahn, Stanley
Abstract : View Supplementary Video 1